Characterization of Zhundong lignite and biomass co-pyrolysis in a thermogravimetric analyzer and a fixed bed reactor. (15th December 2017) - Guo, Feiqiang; Li, Xiaolei; Wang, Yan; Liu, Yuan; Li, Tiantao; Guo, Chenglong
Abstract: The co-pyrolysis characteristics of Zhundong lignite and pine sawdust were investigated in a thermogravimetric analyzer and a fixed bed reactor. This study found that the obtained activation energies were generally lower than the calculated values. Particularly in the conversion range of 0.2–0.6, most of the relative deviation values was lower than −10% for the blends, indicating positive synergistic effect between Zhundong lignite and pine sawdust in volatiles release during non-isothermal pyrolysis. From the isothermal pyroylysis in the fixed bed reactor, the experimental values of gas yield were greater than the calculated, while both experimental tar and char yields became lower. Pronounced synergy effect occurred at ZD and PS mass ratio of 1:1 and 2:1 for tar and gas product, indicating that enough hydrogen-donors could be provided to promote degradation reactions. The experimental yields of four main gas components, CO, H2, CO2 and CH4, were all higher than that of the calculated values. SEM results indicated both Zhundong lignite and pine sawdust residue chars became more porous, and metals salt in Zhundong lignite volatilized and condensed on the surface of Zhundong lignite and pine sawdust, which may perform as catalyst during co-pyrolysis. Highlights: Co-pyrolysis behaviors of biomass and Zhundong lignite was studied. Most of relative deviation of obtained Ea was lower than −10%. Pronounced synergy effect occurred at ZD and PS mass ratio of 1:1 and 2:1. The variation of char surface morphology in co-pyrolysis was studied.